A CASE STUDY ON PRISONERS RIGHT - Naidu, Nirnesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This case study delves into the issue of prisoners' rights, exploring the balance between the rights of individuals incarcerated in prisons and the need for maintaining order and security in correctional facilities. Focusing on the legal framework in India, the study examines how laws, judicial rulings, and international human rights standards interact to safeguard prisoners' rights while ensuring that they serve their sentences. Through an analysis of relevant statutes, landmark court cases, and prison conditions, the study offers a comprehensive review of the current state of prisoners' rights in India, highlighting gaps, challenges, and potential reforms.